#### Chemical Equations Balanced on 01/15/22

 Equations balanced on the previous day Equations balanced on the next day
 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282
Al + HCl = AlCl3 + H2 =>
2 Al + 6 HCl = 2 AlCl3 + 3 H2

HNO3 + HI = H2O + NO2 + HIO3 =>
6 HNO3 + HI = 3 H2O + 6 NO2 + HIO3

C2H5OH + O2 = CO2 + H2O =>
C2H5OH + 3 O2 = 2 CO2 + 3 H2O

NaClO + NH3 = NCl3 + NaOH =>
3 NaClO + NH3 = NCl3 + 3 NaOH

CO2 + H2 = CH3OH + H2O =>
CO2 + 3 H2 = CH3OH + H2O

CO2 + H2O = C6H12O6 + O2 =>
6 CO2 + 6 H2O = C6H12O6 + 6 O2

B2H6 + H2O = H3BO3 + H2 =>
B2H6 + 6 H2O = 2 H3BO3 + 6 H2

Na2O + H2O = NaOH =>
Na2O + H2O = 2 NaOH

C2H6 + O2 = CO2 + H2O =>
2 C2H6 + 7 O2 = 4 CO2 + 6 H2O

H2SO4 + F2 = O2 + HF + SF6 =>
H2SO4 + 4 F2 = 2 O2 + 2 HF + SF6

BaCl2 + Na2SO4 = BaSO4 + NaCl =>
BaCl2 + Na2SO4 = BaSO4 + 2 NaCl

NH3 + O2 = NO + H2O =>
4 NH3 + 5 O2 = 4 NO + 6 H2O

Al + Fe3N2 = AlN + Fe =>
2 Al + Fe3N2 = 2 AlN + 3 Fe

Mg + HCl = MgCl2 + H2 =>
Mg + 2 HCl = MgCl2 + H2

C + O2 = CO2 =>
C + O2 = CO2

Al(OH)3 + H2SO4 = Al2(SO4)3 + H2O =>
2 Al(OH)3 + 3 H2SO4 = Al2(SO4)3 + 6 H2O

K2Cr2O7 + H2C2O4*2H2O = K[Cr(C2O4)2(H2O)2]*2H2O + CO2 + H2O =>
K2Cr2O7 + 7 H2C2O4*2H2O = 2 K[Cr(C2O4)2(H2O)2]*2H2O + 6 CO2 + 13 H2O

K + Br2 = KBr =>
2 K + Br2 = 2 KBr

PH3 + HNO3 = H3PO4 + NO2 + H2O =>
PH3 + 8 HNO3 = H3PO4 + 8 NO2 + 4 H2O

Al + HCl = AlCl3 + H2 =>
2 Al + 6 HCl = 2 AlCl3 + 3 H2

MgF2 + Li2CO3 = MgCO3 + LiF =>
MgF2 + Li2CO3 = MgCO3 + 2 LiF

CH3COOH + CH3CH2OH = CH3COOCH2CH3 + H2O =>
CH3COOH + CH3CH2OH = CH3COOCH2CH3 + H2O

C5H10 + O2 = CO2 + H2O =>
2 C5H10 + 15 O2 = 10 CO2 + 10 H2O

NH4ClO4 + Al = Al2O3 + HCl + H2O + N2 =>
6 NH4ClO4 + 10 Al = 5 Al2O3 + 6 HCl + 9 H2O + 3 N2

BaS + Na2SO4 = BaSO4 + Na2S =>
BaS + Na2SO4 = BaSO4 + Na2S

Pb(NO3)2 + Na2SO4 = PbSO4 + NaNO3 =>
Pb(NO3)2 + Na2SO4 = PbSO4 + 2 NaNO3

LiOH + CO2 = Li2CO3 + H2O =>
2 LiOH + CO2 = Li2CO3 + H2O

H2O2 = H2O + O2 =>
2 H2O2 = 2 H2O + O2

CH4 + H2O + N2 = NH3 + CO =>
CH4 + H2O + N2 = 2 NH3 + CO

BaS + Na2SO4 = BaSO4 + Na2S =>
BaS + Na2SO4 = BaSO4 + Na2S

MnO2 + KClO3 + KOH = K2MnO4 + KCl + H2O =>
3 MnO2 + KClO3 + 6 KOH = 3 K2MnO4 + KCl + 3 H2O

Fe(NO3)3 + Na2(CO3) = Fe2(CO3)3 + Na(NO3) =>
2 Fe(NO3)3 + 3 Na2(CO3) = Fe2(CO3)3 + 6 Na(NO3)

P4(s) + H2(g) = PH3(g) =>
P4(s) + 6 H2(g) = 4 PH3(g)

CH3OH + O2 = CO2 + H2O =>
2 CH3OH + 3 O2 = 2 CO2 + 4 H2O

Ag2S = Ag + S8 =>
8 Ag2S = 16 Ag + S8

P4 + O2 = P2O5 =>
P4 + 5 O2 = 2 P2O5

Cu + FeSO4 = CuSO4 + Fe =>
Cu + FeSO4 = CuSO4 + Fe

Cd(NO3)2 + NaOH = Cd(OH)2 + NaNO3 =>
Cd(NO3)2 + 2 NaOH = Cd(OH)2 + 2 NaNO3

P4 + O2 = P2O3 =>
P4 + 3 O2 = 2 P2O3

CaCO3 = CaO + CO2 =>
CaCO3 = CaO + CO2

Ba(NO3)2(aq) + (NH4)2SO4(aq) = BaSO4(s) + NH4NO3(aq) =>
Ba(NO3)2(aq) + (NH4)2SO4(aq) = BaSO4(s) + 2 NH4NO3(aq)

Al(OH)3 + H2SO4 = Al2(SO4)3 + H2O =>
2 Al(OH)3 + 3 H2SO4 = Al2(SO4)3 + 6 H2O

O2 + NH3 + CH4 = H2O + HCN =>
3 O2 + 2 NH3 + 2 CH4 = 6 H2O + 2 HCN

Zn + O2 = ZnO =>
2 Zn + O2 = 2 ZnO

NH4ClO4 = N2 + Cl2 + O2 + H2O =>
2 NH4ClO4 = N2 + Cl2 + 2 O2 + 4 H2O

BF3 + Li2(SO3) = B2(SO3)3 + LiF =>
2 BF3 + 3 Li2(SO3) = B2(SO3)3 + 6 LiF

NaHCO3 = NaOH + CO2 =>
NaHCO3 = NaOH + CO2

BaS + Na2SO4 = BaSO4 + Na2S =>
BaS + Na2SO4 = BaSO4 + Na2S

BaS + Na2SO4 = BaSO4 + Na2S =>
BaS + Na2SO4 = BaSO4 + Na2S

BaS + Na2SO4 = BaSO4 + Na2S =>
BaS + Na2SO4 = BaSO4 + Na2S

 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282